An Introduction to the Study of Isaiah. Approaches to Biblical Studies, Jacob Stromberg : book review - Weber, Beat (Old Testament essays, 2012)
This book by Jacob Stromberg, lecturer at the University of North Carolina at Chapel Hill, USA forms part of the series T&T Clark Approaches to Biblical Studies. The importance the book of Isaiah had for Christians over centuries and still has hardly needs mentioning. The same goes for the high esteem it has amongst lay people, clergy and scholars alike. No wonder JFA Sawyer (1996) gave his monograph on Isaiah the title "The Fifth Gospel." One just has to look for instance at the extent of secondary literature with regard to Isaiah since the days Bernard Duhm's epoch making commentary of 1892 to realize how important the interpretation of this book has been for Old Testament scholars, clergy and lay people.